2020
DOI: 10.3390/su12041504
|View full text |Cite
|
Sign up to set email alerts
|

Does the Mark-to-Model Fair Value Measure Make Assets Impairment Noisy?: A Literature Review

Abstract: With the purpose of reporting high-quality, transparent, and comparable information in financial statements, there is a strong, visible trend towards the implementation and use of International Financial Reporting Standards (IFRS), which represent the Anglo-American accounting model. According to IFRS, the fair value has become a dominant measurement paradigm. The purpose of this paper is to examine the implications of the implementation of the mark-to-model fair value measures for asset impairment tests on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
0
9
0
1
Order By: Relevance
“…Additionally, in a research, the implications of the implementation of the mark-tomodel fair value measures for asset impairment tests on the relevance and reliability of information presented in financial reports were examined (Dudycz and Praznikow 2021). They concluded that the implementation of asset impairment tests that use the mark-tomodel fair value measures is not promising for increasing the quality and reliability of the information presented in financial statements.…”
Section: Impairment Of Assets and Market Reaction-literature Overviewmentioning
confidence: 99%
“…Additionally, in a research, the implications of the implementation of the mark-tomodel fair value measures for asset impairment tests on the relevance and reliability of information presented in financial reports were examined (Dudycz and Praznikow 2021). They concluded that the implementation of asset impairment tests that use the mark-tomodel fair value measures is not promising for increasing the quality and reliability of the information presented in financial statements.…”
Section: Impairment Of Assets and Market Reaction-literature Overviewmentioning
confidence: 99%
“…Previous research showed that among the three levels of the fair value hierarchy, mark-to-model is most controversial because it is susceptible to manipulation and has poor verifiability. Previous research concluded that the implementation of asset impairment tests, that use the mark-to-model fair value measures, is not promising for increasing the quality and reliability of the information presented in financial statements [18].…”
Section: Prior Research and Hypothesismentioning
confidence: 99%
“…Fixed asset revaluation (FAR) is the formal process of restating the book value of an asset to its fair value (Brown et al, 1992;Rafay et al, 2019). The users of financial statements acknowledge the fair value of assets as more relevant to make apposite investments and other decisions (Barac and Sodan, 2011;Chea, 2011;Dudycz and Praźników, 2020). By providing fair value information of fixed assets, FAR helps reduce information asymmetry that, in turn, minimizes the opportunistic behavior of the management and facilitates accurate investment decisions (Zakaria et al, 2014).…”
Section: Introductionmentioning
confidence: 99%